The impact of a pandemic on dental professionals' work and personal lives: A qualitative study with implications for primary healthcare workers - Al-Amer, Rasmieh; Ramjan, Lucie M.; Maneze, Della; Al-Rashdan, Omar; Villarosa, Amy R.; Salamonson, Yenna; George, Ajesh (Frontiers in Public Health, 2022)
Introduction: During a pandemic, dentists face enormous challenges due to restrictions placed on their practice and the need to comply with biosafety measures. Aim: This study aimed to explore the impact of the COVID-19 pandemic and infection control measures on dentists and their practice in Jordan and the global implications for other primary healthcare workers. . Methods: One-on-one face-to-face or telephone interviews were conducted with ten dentists from the 9th of May to 20th September 2020. Findings: Stringent infection control measures were implemented to slow the spread of the virus, however limited government support made implementation unsustainable and caused financial hardship. Lack of clear guidelines, changes in practice, social distancing measures, and altered social interactions, adversely impacted daily life, triggering mental distress. Misinformation influenced response to COVID safety measures. Despite the negatives, working during the pandemic reaffirmed dental professionals’ roles and purpose, with strong leadership boosting morale. Discussion: Giving voice to healthcare professionals most affected by the pandemic, like dentists, is important. Implication for healthcare providers and Health Policy: Establishment of a health policy in relation to providing adequate biosafety resources to support and sustain stringent infection control procedures are crucial in safeguarding their health and that of the community. Promoting the mental health and wellbeing of the healthcare workforce is equally essential in a pandemic response.